2008
DOI: 10.1128/jvi.01936-07
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sindbis Virus Capsid Protein Region II in Nucleocapsid Core Assembly and Encapsidation of Genomic RNA

Abstract: Sindbis virus is an enveloped positive-sense RNA virus in the alphavirus genus. The nucleocapsid core contains the genomic RNA surrounded by 240 copies of a single capsid protein. The capsid protein is multifunctional, and its roles include acting as a protease, controlling the specificity of RNA that is encapsidated into nucleocapsid cores, and interacting with viral glycoproteins to promote the budding of mature virus and the release of the genomic RNA into the newly infected cell. The region comprising amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…1A). This conserved, VEEV CP-specific peptide (helix 2) was previously proposed to fold into a short ␣-helix (21) and to be involved in binding to the ribosomes, and recognition of viral genomic RNA (9,22). Multiple functions proposed for helix 2 need further, more detailed investigation, which is beyond the scope of the present study.…”
Section: Resultsmentioning
confidence: 76%
“…1A). This conserved, VEEV CP-specific peptide (helix 2) was previously proposed to fold into a short ␣-helix (21) and to be involved in binding to the ribosomes, and recognition of viral genomic RNA (9,22). Multiple functions proposed for helix 2 need further, more detailed investigation, which is beyond the scope of the present study.…”
Section: Resultsmentioning
confidence: 76%
“…Two copies of this sequence were present in the SINV DI RNA genome (26,28,39), and their deletion had a negative effect on RNA encapsidation, but not on RNA replication. Further studies strongly suggested that the interaction of this PS with SINV capsid is mediated by a short amino acid sequence located between amino acids (aa) 96 and 107 of the SINV capsid protein (29,43). These data provided a plausible explanation for specific packaging of SINV genomic RNA.…”
Section: Discussionmentioning
confidence: 98%
“…The carboxy terminus of the H68 peptide contains a short sequence of positively charged amino acids that might serve as an NLS. This sequence is a part of the large positively charged domain (aa 64 to 117 of the capsid) that is involved in encapsidation of viral genomic RNA (18,48) and contains a number of positively charged peptides, which, based on the computer prediction, may serve as NLS. Previously, we isolated a frameshift mutant of VEEV capsid protein, C VEE frsh ( Fig.…”
Section: Resultsmentioning
confidence: 99%